5x+12-18=10x-16+23z

Simple and best practice solution for 5x+12-18=10x-16+23z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+12-18=10x-16+23z equation:


Simplifying
5x + 12 + -18 = 10x + -16 + 23z

Reorder the terms:
12 + -18 + 5x = 10x + -16 + 23z

Combine like terms: 12 + -18 = -6
-6 + 5x = 10x + -16 + 23z

Reorder the terms:
-6 + 5x = -16 + 10x + 23z

Solving
-6 + 5x = -16 + 10x + 23z

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-6 + 5x + -10x = -16 + 10x + -10x + 23z

Combine like terms: 5x + -10x = -5x
-6 + -5x = -16 + 10x + -10x + 23z

Combine like terms: 10x + -10x = 0
-6 + -5x = -16 + 0 + 23z
-6 + -5x = -16 + 23z

Add '6' to each side of the equation.
-6 + 6 + -5x = -16 + 6 + 23z

Combine like terms: -6 + 6 = 0
0 + -5x = -16 + 6 + 23z
-5x = -16 + 6 + 23z

Combine like terms: -16 + 6 = -10
-5x = -10 + 23z

Divide each side by '-5'.
x = 2 + -4.6z

Simplifying
x = 2 + -4.6z

See similar equations:

| -4/3*x=1 | | -3(2s-2)-6=-3(5s+6)-4 | | -2.6(2.19)= | | -2x+7y=-32 | | 2/3(x-7)=-16 | | 10p-14=9p+7 | | x-58=16x+24-17 | | 2x+118+2x+68=186 | | 50=-2t^3+23t^2-59t+24 | | Y=15+10x | | 0.5(x-40)=6+7x | | t(m)=x^2+6x+5 | | (Y+2)-(5y-2)= | | 1=x*-4/3 | | X*x+.08x-.024=0 | | 20=5m+12 | | (2a+2h+5)(2a+5)=0 | | P=-10x^2+215x+3700 | | 2x+6y-5=j | | 4x+6=5x-10 | | 2y^2+64=22 | | -5+7x+16+x=11x-3-3 | | ln(2x+4)=7 | | -3(2x+1)+7x= | | -4(3c+8)=-3(4c-10) | | 2y^2+32=22 | | -5(4x+2)+21x= | | .2x-.8y=0 | | 4d-28=-34 | | 6s+9=-4a+29 | | 45/x=9/2 | | M-11=18 |

Equations solver categories